McCune-Albright Syndrome: Evaluation of Craniofacial Involvement Through Magnetic Resonance Images - Poma Carmona, Augusto (1999)
We report the case of a male teenager with the classical clinical picture of McCune-Albright syndrome, with precocious puberty, cafe-au-lait spots, polyostotic fibrous dysplasia and gigantism. Magnetic resonance images are described and a review of the respective literature is also presented.